Attitude toward human papillomavirus self-sampling and associated factors among Thai women undergoing colposcopy - Pichamon Sukkasame; Nida Jareemit; Awassada Punyashthira; Perapong Inthasorn; Nopwaree Chantawong; Komsun Suwannarurk; Piyawan Pariyawateekul; Siriwan Tangjitgamol; Thai Gynecologic Cancer Society Research Group (Korean Society of Obstetrics and Gynecology, 2024)
Objective To compare attitudes toward self-sampling for human papillomavirus (HPV) testing before and after specimen collection in women undergoing colposcopy. The factors associated with the pre-sampling attitude were also studied. Methods This prospective study enrolled women with abnormal cervical cytology and/or positive high-risk HPV who attended colposcopy clinics at 10 cancer centers in Thailand between October 2021 and May 2022. Prior to colposcopy, the attitudes of the women toward self-sampling were surveyed through a questionnaire. Written and verbal instructions for self-sampling were provided before the process and subsequent colposcopy. The attitudes toward self-sampling were reassessed after the actual self-sampling. Factors associated with the attitudes were analyzed. Results A total of 499 women were included in this study. The mean age was 39.28±11.36 years. A total of 85.3% were premenopause, and 98.8% had sexual experience. With the full score of 45, the attitude score after self-sampling was significantly higher than the attitude score before self-sampling (39.69±5.16 vs. 37.76±5.71; P<0.001). On univariate analysis, the factors associated with attitude before HPV self-sampling were age, menopausal status, sexual activity, education level, income, knowledge regarding HPV, and prior high-grade squamous intraepithelial lesion histology. The remaining significant factor on multivariate analysis was sexual activity within the past year (B=0.105, 95% confidence interval, 0.014-2.870; P=0.048). Conclusion Attitudes toward self-sampling improved after the actual self-sampling process, as evidenced by higher attitude scores. Sexual activity was the only independent factor related to the attitude before self-sampling.